Algebro-Geometric Solutions to a New Hierarchy of Soliton Equations - Wang, H.; Geng, X. (Журнал математической физики, анализа, геометрии, 2015)
With the help of the Lenard recursion equations, we derive a new hierarchy of soliton equations associated with a 3×3 matrix spectral problem and establish Dubrovin type equations in terms of the introduced trigonal curve Km-1 of arithmetic genus m - 1. Basing on the theory of algebraic curve, we construct the corresponding Baker-Akhiezer functions and meromorphic functions on Km-1. The known zeros and poles for the Baker-Akhiezer function and meromorphic functions allow us to find their theta function representations, from which algebro-geometric constructions and theta function representations of the entire hierarchy of soliton equations are obtained. С помощью рекуррентных уравнений Ленарда получена новая иерархия солитонных уравнений, связанных с 3×3 матричной спектральной задачей, и установлены уравнения типа Дубровина в терминах представленной тригональной кривой Km-1 арифметического рода m - 1. Основываясь на теории алгебраических кривых, построены соответствующие функции Бейкера- Ахиезера и мероморфные функции на Km-1. Известные нули и полюсы для функций Бейкера-Ахиезера и мероморфных функций позволяют найти их представления в тета-функциях, из которых получены алгебро-геометрические конструкции и представления в тета-функциях решений всей иерархии солитонных уравнений.